Penundaan Kematangan Menggunakan Oksidan Etilen dan Pengaruhnya Terhadap Perubahan Fisiologi Pisang Barangan - Agustiningrum, Dyah Ayu; Darmawati, Emmy; Widayanti, Siti Mariana (Jurnal Keteknikan Pertanian, 2019)
AbstractEthylene oxidants were used to delay Barangan banana ripening at ambient temperature. However, a few information about the effect of ripening delay to fruit physiological quality after treatment that has been reported. This study was performed to examine the effects of ripening delay using ethylene oxidants to fruit quality during storage, ripening process, and display period. The experimental design was usedrandomize complete design with two factors consisting 2 levels of picking date and 3 levels of delaying duration. Ethylene oxidants (KMnO4 and zeolite powder) were packaged into sachets and applied to banana packaging. Observed quality parameters were peel color, hardness and TSS content. The results indicated that ethylene oxidants application effectively delayed Barangan banana ripening at 25±2°C compared to control. Banana picked at 10 weeks after flower cutting (WAFC) has longer green life period than 11 WAFC. Ripening delay treatment did not detrimentally affect fruits quality. The fruits ripened normally and attain optimum TSS as the control. Overall, the quality parameters at the display period were not significantly different (α